Study of radiation-chemical structuring of compositions based on epoxy oligomers - Podhornaya, L. F.; Avramenko, V. L.; Karandashov, O. H. (V. N. Karazin Kharkiv National University, 2020)
The processes of radiation-chemical structuring of modified epoxy acrylic compositions were studied depending on the nature of epoxy oligomers and modifiers. ED-20 and ED-22 grades epoxy oligomers were chosen as epoxidian oligomers; 3,4-epoxyhexahydrobenzal-3,4-epoxy-1,1-bis(hydroxymethyl)cyclohexane (UP-612 grade), 3,4-epoxycyclohexylmethyl-3,3-epoxycyclohexanecarboxylate (UP-632 grade) were chosen as cycloaliphatic oligomers; diethylene glycol diglycidyl ether (DEG) was chosen as aliphatic oligomer. To modify the epoxy oligomers, unsaturated acrylic monomers, such as acrylic acid and methyl acrylic acid ester; aromatic and aliphatic oligoester acrylates, such as α,ω-methacryl(bis-diethylene glycol)phthalate (MDP-1 grade), α,ω-methacryldi(diethyleneglycolphthalate) (MDP-2 grade), α,ω-methacryl(bis-triethyleneglycol)phthalate (MGP-9 grade) and atri-(oxyethylene)-α,ω-dimethacrylate (TGM-3 grade); condensation product of linseed oil dimerized fatty acids and polyethylenepolyamine, such as oligoamide L-20 grade; condensation product of ricinoleic acid, castor oil and maleic anhydride, such as unsaturated polyester PE-220, were used. The thermophysical and relaxation properties of cross-linked polymers, obtained under exposure to γ-radiation of Co60 and electrons accelerated by the absorbed radiation dose of 50–150 kGy at the beam current of 2-4 mA and electron energy of 240-300 keV, were studied. The distance from the exhaust window of the accelerator to the irradiated surface of the samples was 63-80 mm. The thermophysical properties of the cured polymers were evaluated using thermomechanical studies on a thermomechanograph with the temperature rise of 1о/min and the pressure of 0.54 MPa in the temperature range of 293-673 K, as well as the differential thermal and thermogravimetric analyzes on a system derivatograph by L. Paulik, R. Paulik, L. Erdei in the temperature range of 293–973 K with the rise rate of 7о/min. The relaxation properties and molecular mobility of the cross-linked polymers were studied by the dielectric method. The dielectric loss tangent was determined in the temperature range of 143-393K at the frequency of 1 kHz using a digital automatic bridge of alternating current R-589. The test sample temperature was measured using a potentiometer on a copper-constantan thermocouple, which was placed in the measuring cell along with the test sample. The samples were cooled by placing the cell in a vessel with liquid nitrogen. As a result of the studies, the influence of the chemical nature of epoxy oligomers and unsaturated modifiers on the processes of structure formation and molecular mobility of polymers, obtained under conditions of radiation-chemical curing, was established. It was determined, that when modifying epoxy oligomers with acrylic acid, methyl acrylic acid ester, oligoester acrylates of MGP-9 ((α,ω-methacryl(bistriethyleneglycol) phthalate)) or TGM-3 ((tri-(oxyethyleneglicol)-α,ω-dimethacrylate)) grades, the structuring of compositions, based on the DEG-1 aliphatic epoxy oligomer and UP-612 cycloaliphatic oligomer, was more efficient than the compositions based on unsaturated ETO oligomers grade such as 2-ethylhexylepoxytallate oligomer and epoxidian oligomers of ED-20 and ED-22 grades. It was established, that the modifier oligoamide of L-20 grade, containing primary and secondary amino groups, increased the radiation sensitivity of the compositions, based on epoxidian and cycloaliphatic oligomers, and reduced the inhibitory effect of atmospheric oxygen. The optimal composition and the main technological parameters were determined, what allowed to obtain materials with high physical and mechanical properties and adhesive strength to various metals. The application of the developed materials under industrial conditions will make it possible to organize a continuous high-speed radiation-chemical process for producing polymer coatings on metals, providing improved working conditions, lower energy consumption, as compared to the thermochemical process of the coatings production, and will increase the corrosion resistance of metals.

Досліджено процеси радіаційно-хімічного структурування модифікованих епоксіакрілових композицій в залежності від природи епоксидних олігомерів і модифікаторів. У якості епоксидних олігомерів були обрані епоксидіанові олігомери марок ЕД-20, ЕД-22; у якості циклоаліфатичних олігомерів були обрані 3,4-епоксигексагідробензаль-3,4-епокси 1,1-біс-(гідроксиметил) -ціклогексан, марки УП-612, а також 3,4-епоксиціклогексілметіл-3,3-епоксициклогексанкарбоксілат, марки УП-632; і дігліціділовий ефір діетиленгліколю ДЕГ був обраний в якості аліфатичного олігомера. Для модифікації епоксидних олігомерів використовували: ненасичені акрилові мономери, такі як акрилова кислота та складний ефір метілакрилової кислоти; ароматичні і аліфатичні олігоефірні акрилати, такі як α, ω-метакрил (біс-діетиленгліколь) фталат (марки MDP-1), α, ω-метакрілді (діетиленглікольфталат) (марки MDP-2), α, ω-метакрил (біс-триетиленгліколь )) фталат (марки MGP-9), три- (оксіетиленгліколь) -α, ω-диметакрилат (марка TGM-3); продукт конденсації дімерізованних жирних кислот лляної олії і поліетиленполіамін, такого як олігоамід марки L-20; продукт конденсації рицинолевої кислоти, касторової олії і малеїнового ангідриду, такого як ненасичений поліефір PE-220. Вивчено теплофізичні і релаксаційні властивості сітчастих полімерів, отриманих під дією γ-випромінювання Со60 і електронів, прискорених поглиненою дозою випромінювання 50-150 кГр при струмі в пучку 2-4 мА і енергії електронів 240-300 кеВ. Відстань від випускного вікна прискорювача до опромінюваної поверхні зразків становила 63-80 мм. Теплофізичні властивості затверділих полімерів оцінювали за допомогою термомеханічних досліджень на термомеханографі при підйомі температури 1о/хв і тиску 0,54 МПа в інтервалі температур 293-673К, а також методом диференціального термічного і термогравіметричного аналізів на дериватографі системи Л. Паулік, Р. Паулік, Л. Ердеі в інтервалі температур 293-973 К зі швидкістю підйому 7о/хв. Релаксаційні властивості і молекулярну рухливість сітчастих полімерів вивчали діелектричним методом. Визначення тангенса кута діелектричних втрат здійснювали в температурному інтервалі 143-393К при частоті 1 кГц цифровим автоматичним мостом змінного струму Р-589. Вимірювання температури досліджуваного зразка проводили за допомогою потенціометра від термопари мідь-константан, яка перебувала у вимірювальному відсіку разом із досліджуваним зразком. Охолодження зразків здійснювали шляхом розміщення відсіку в посудину з рідким азотом. В результаті досліджень встановлено вплив хімічної природи епоксидних олігомерів і ненасичених модифікаторів на процеси формування структури і молекулярну рухливість полімерів, отриманих в умовах радіаційно-хімічного затвердіння. Визначено, що при модифікації епоксидних олігомерів акриловою кислотою, метиловим ефіром акрилової кислоти, олігоефіракрилатом МГФ-9 або ТГМ-3 структурування композицій на основі аліфатичного епоксиолігомера ДЕГ-1 і циклоаліфатичного олігомера УП-612 здійснюється більш ефективно у порівнянні з композиціями на основі ненасиченого олігомеру ОЕТ і епоксидіанових олігомерів ЕД-20 і ЕД-22. Встановлено, що модифікатор олігоамід Л-20, що містить первинні і вторинні аміногрупи, підвищує радіаційну чутливість композицій на основі епоксидіанових і циклоаліфатичних олігомерів і зменшує інгібуючу дію кисню повітря. Визначено оптимальний склад композицій та основні технологічні параметри, що дозволяють отримувати матеріали з високими фізико-механічними властивостями і адгезійною міцністю до різних металів. Застосування розроблених матеріалів у промислових умовах дозволить організувати безперервний високошвидкісний радіаційно-хімічний процес отримання полімерних покриттів на металах з поліпшеними умовами праці, меншими енерговитратами в порівнянні з термохімічним процесом отримання покриттів, і забезпечить підвищення корозійної стійкості металів.
Дослідження радіаційно-хімічного структурування композицій на основі епоксидних олігомерів
Keywords: radiation-chemical structuring; ionizing radiation; differential thermal analysis; macromolecule; epoxy oligomer; іонізуюче випромінювання; диференційно-термічний аналіз; макромолекули; хімічні реакції; фізико-механічні властивості